Effectiveness of Archive Services Using “Si Artis” In Kebumen Regency, Indonesia - Setiadi, Bayu Galih; Fernandus, Yossa; Effendi, Lina Marlina (Indonesian Journal of Librarianship, 2022)
Background: This research determines the effectiveness of the Si Artis application in the Kebumen Regency Archives and Libraries Service as an innovation in the use of information technology in archival services. Method: The method used is descriptive and qualitative, and 4 dimensions were used to evaluate effectiveness. These include organization, management, technology, and expertise. Result: The results showed that on the organizational dimension, only corporate structure indicators were satisfied, while policy indicators in the application of information systems were lacking. This was evidenced by the lack of submissions to the department. The management dimension was optimal, and can only be met by the system's ability to provide information. Furthermore, supporting facilities in the form of application databases were lacking due to continuous control by developers. In the expertise dimension, the employees’ ability to operate the system was fulfilled, but technological expertise was lacking because there were no IT experts hired by the agency. Conclusion: Despite several shortcomings, archival service through the Si Artis application was significantly effective. Therefore, it represents an innovation in archiving services in Kebumen Regency. Keywords: Archive Application, "Si Artis", Archive Services, Service Innovation, Government Applied Technology